Quality‐of‐life outcomes of initiating treatment with standard and newer antiepileptic drugs in adults with new‐onset epilepsy: Findings from the SANAD trial. (29th January 2015) - Jacoby, Ann; Sudell, Maria; Tudur Smith, Catrin; Crossley, Joanne; Marson, Anthony G.; Baker, Gus A.; ,
Summary: Objective: To compare quality‐of‐life (QoL) outcomes over 2 years following initiation of treatment with a standard or newer antiepileptic drug (AED) in adults with new‐onset epilepsy. To examine the impact of seizure remission and failure of initial treatment on QoL outcomes measured over 2 years. Methods: We conducted a pragmatic, randomized, unblinded, multicenter, parallel‐group clinical trial (the Standard and New Antiepileptic Drugs [SANAD] trial) comparing clinical and cost effectiveness of initiating treatment with carbamazepine versus lamotrigine, gabapentin, oxcarbazepine and topiramate, and valproate versus lamotrigine and topiramate. QoL data were collected by mail at baseline, 3 months, and at 1 and 2 years using validated measures. These data were analyzed using longitudinal data models. Continuous QoL measures, time to 12‐month remission and time to treatment withdrawal were explored using joint models. Results: Baseline questionnaires were returned by 1, 575 adults; 1, 439 returned the 3‐month questionnaire, 1, 274 returned the 1‐year questionnaire, and 1, 121 returned the 2‐year questionnaire. There were few statistically significant differences between drugs over 2 years in QoL outcomes. Significant association was identified between QoL scores over the 2‐year time frame and the risk of experiencing a 12‐month remission or treatment withdrawal over that period. Significance: The choice of initial treatment had no significant effect on QoL by 2‐year follow‐up. However, overall QoL was reduced with continued seizures, adverse events, and failure of the initial treatment.